Perkembangan Wakaf Produktif dalam Analisis Bibliometrik - Ulum, Miftachul; Mun'im, Abdul (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2025)
The purpose of this study is to capture the development of research on waqf and to determine the direction of future research. The research method is based on data based on Scopus indexed publications using the Publish or Perish, Excel and VOSViewer applications in Bibliometric analysis. The results of the study show that the dominance of publications with the theme of waqf is still dominated by countries with Muslim populations. Malaysia, Indonesia and Turkey are 3 countries that dominate publications with the theme of waqf. Publication themes that can be prioritized in future publications include the theme of productive waqf with Islamic social finance. Researchers can create a link between the two themes in a publication.